Modified silane coupling agent and method for treating laminated foil

By combining the modified silane coupling agent with components such as hydroxyl-containing resin and aluminum powder to prepare the sintered layer slurry, the problems of poor bending resistance, hydration resistance and leakage performance of the accumulated foil are solved, and higher capacitor stability and working efficiency are achieved.

CN119505232APending Publication Date: 2025-02-25XINJIANG JINTAI NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411627298.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The etching process of existing aluminum electrolytic capacitors is very polluted to the environment, and the bending resistance, hydration resistance and leakage performance of the accumulated foil are poor, which affects the stability and working efficiency of the capacitor.

Method used

Using a modified silane coupling agent, with a star topology and siloxane terminal functional groups, a sintered layer slurry is prepared by combining with components such as hydroxyl-containing resin and aluminum powder, and a layered foil is prepared by coating and sintering processes.

Benefits of technology

The bending resistance, hydration resistance and leakage performance of the accumulated foil are improved, the stability and working efficiency of the capacitor are enhanced, and the pollution to the environment is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005135059940000111
    Figure BDA0005135059940000111
Patent Text Reader

Abstract

The invention relates to a modified silane coupling agent with a star-shaped topological structure, a functional group at the tail end of the modified silane coupling agent is a siloxane group, the star-shaped topological structure is defined as that three or more linear branched chains are sequentially connected to a central core, and functional groups at the tail ends of the linear branched chains are siloxane groups. The silane coupling agent is matched with resin to serve as a binder to prepare sintering layer slurry, the modified silane coupling agent of a star topological structure provides more reaction sites between inorganic matter and organic resin, the modified silane coupling agent is coated on an oxidation film on the surface of aluminum foil to fill defects of the aluminum foil, the coating effect is better, and the service life of the aluminum foil is prolonged. Therefore, the prepared laminated foil has higher bending resistance, hydration resistance and electric leakage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of advanced functional materials, and particularly relates to a modified silane coupling agent and a method for processing laminated foil. Background Art

[0002] With the development of electronic technology, electrolytic capacitors, as discrete components that cannot be integrated into electronic products, are currently developing in the direction of small size, large capacity, low cost, high frequency and low impedance. Among them, aluminum electrolytic capacitors have the characteristics of excellent performance, large capacity, low price, easy processing, and convenient use. Therefore, they are widely used in electronic equipment, instruments, electromechanical, home appliances and other electronic products. However, the preparation process of aluminum electrolytic capacitors is complicated. Aluminum foil is used as the raw material. After etching, etching pits are formed to increase its surface area. After chemical treatment, an oxide film is formed on the surface of the aluminum foil. This oxide film is the dielectric of the aluminum electrolytic capacitor. However, in the etching process, a hydrochloric acid aqueous solution containing sulfuric acid, phosphoric acid, nitric acid, etc. is required, which has a great impact on the environment, especially the economic cost of treating acid-containing wastewater is very high.

[0003] In order to improve the defect of etching process that causes high environmental pollution, laminated foil is currently obtained by adhering fine aluminum powder or fine aluminum alloy powder to the surface of aluminum foil through sintering. However, compared with the electrode foil obtained by etching, the laminated foil has poor bending resistance and leakage performance. In particular, the voltage rise time in the hydration resistance test is significantly slowed down after soaking in water, which is more obvious when preparing high-capacity electrode foil. It is also easy to cause powder loss and excessive leakage current. These problems affect the stability and working efficiency of capacitors prepared by laminated foil. Summary of the invention

[0004] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a modified silane coupling agent, thereby preparing a sintered layer slurry, and on this basis preparing a laminated foil and improving its bending resistance, hydration resistance and leakage performance.

[0005] In a first aspect, a modified silane coupling agent has a star topology structure, and the functional group at its end is a siloxane group, wherein the star topology structure is defined as 3 or more linear branches connected in sequence to a central core, and the functional group at the end of the linear branch is a siloxane group.

[0006] Furthermore, the modified silane coupling agent is obtained by reacting a polyamine having a star topology structure with an epoxy-containing silane coupling agent or an isocyanate-containing silane coupling agent;

[0007] Preferably, the modified silane coupling agent is obtained by reacting a polyamine having a star topology structure with an isocyanate-containing silane coupling agent.

[0008] Preferably, the polyamine having a star-shaped topology is an amino-terminated polyamide-amine dendrimer;

[0009] Preferably, the epoxy-containing silane coupling agent is glycidyloxypropyltrimethoxysilane (KH-560);

[0010] Preferably, the isocyanate-containing silane coupling agent is isocyanatepropyltriethoxysilane (IPTS).

[0011] Furthermore, the modified silane coupling agent is obtained by reacting a polyol having a star topology structure with an isocyanate-containing silane coupling agent;

[0012] Preferably, the polyol having a star topology is a hydroxyl-terminated polyamide-amine type dendrimer;

[0013] Preferably, the isocyanate-containing silane coupling agent is isocyanatepropyltriethoxysilane (IPTS).

[0014] Furthermore, the modified silane coupling agent is obtained by reacting a polyacid having a star topology structure with an epoxy-containing silane coupling agent;

[0015] Preferably, the polyacid having a star-shaped topological structure is a carboxyl-terminated polyamide-amine type dendrimer;

[0016] Preferably, the epoxy-containing silane coupling agent is glycidyloxypropyltrimethoxysilane (KH-560).

[0017] Furthermore, the modified silane coupling agent is obtained by reacting a polyglycidyl ether having a star topology structure with a silane coupling agent containing an amino group or an imino group;

[0018] Preferably, the polyglycidyl ether having a star topology structure includes any one or more combinations of trimethylolpropane triglycidyl ether, triglycidyl isocyanurate and triglycidyl p-aminophenol;

[0019] Preferably, the amino- or imino-containing silane coupling agent is any one or more combinations of aminopropyltrimethoxysilane, aminopropyltriethoxysilane, bis(3-trimethoxysilylpropyl)amine or bis(3-triethoxysilylpropyl)amine.

[0020] Furthermore, the modified silane coupling agent is obtained by reacting a polyisocyanate having a star topology structure with a silane coupling agent containing an amino group or an imino group;

[0021] Preferably, the polyisocyanate having a star topology structure includes any one or more combinations of TDI trimer, TDI pentamer, IPDI trimer or HDI trimer;

[0022] Preferably, the amino- or imino-containing silane coupling agent is selected from any one or more combinations of aminopropyltrimethoxysilane, aminopropyltriethoxysilane, bis(3-trimethoxysilylpropyl)amine or bis(3-triethoxysilylpropyl)amine.

[0023] In a second aspect, the method for preparing the modified silane coupling agent having a star-shaped topological structure comprises: grafting the silane coupling agent onto a central core having a star-shaped topological structure through a reaction;

[0024] Preferably, the groups for grafting reaction between the silane coupling agent and the central core include: epoxy, carboxyl, hydroxyl, isocyanate, amino or imino groups;

[0025] More preferably, the groups for grafting reaction between the silane coupling agent and the central core include: isocyanate, amino or imino;

[0026] Preferably, the grafting reaction includes but is not limited to: reaction of epoxy group with amino group or imino group, reaction of epoxy group with carboxyl group, reaction of amino group or imino group with isocyanate group, reaction of hydroxyl group with isocyanate group;

[0027] More preferably, the grafting reaction comprises a reaction between an amino group or an imino group and an isocyanate group.

[0028] Preferably, the total molar amount of reactive groups on the silane coupling agent is greater than or equal to the total molar amount of reactive groups on the central core.

[0029] In a third aspect, a sintering layer slurry comprises: the modified silane coupling agent described above, a hydroxyl-containing resin, aluminum powder or aluminum alloy powder and a solvent;

[0030] The hydroxyl-containing resin includes: one or more combinations of polyvinyl alcohol resin, polyester resin, epoxy resin, phenolic resin, phenolic epoxy resin, and hydroxyl acrylic resin;

[0031] The solvent includes one or more of methanol, ethanol, isopropanol, ethylene glycol, glycerol, ethyl acetate, and butyl acetate;

[0032] Preferably, the particle size of the aluminum powder or aluminum alloy powder is in the range of 100 nm to 10 μm;

[0033] Preferably, the solid content of the sintering layer slurry is 50-70%, and more preferably, the solid content of the sintering layer slurry is 55-65%;

[0034] Preferably, in order to improve the sintering performance, the sintering layer slurry further comprises a nonionic surfactant, and more preferably, the nonionic surfactant is polyethylene glycol PEG;

[0035] In a fourth aspect, a method for preparing a laminated foil comprises: coating the sintering layer slurry described above on at least one side of a substrate, and then gradually increasing the temperature for sintering, wherein the substrate is an aluminum foil.

[0036] Furthermore, the method for preparing the laminated foil comprises the following specific steps:

[0037] S1. Pretreatment of the substrate: remove oil stains on the substrate surface, and use 0.1M dilute hydrochloric acid or dilute sulfuric acid to slightly corrode and remove the metal oxide film on the substrate surface;

[0038] Preferably, in step S1, 0.1M dilute hydrochloric acid is used to slightly corrode and remove the metal oxide film on the surface of the substrate;

[0039] S2. Preparation of sintering layer slurry: uniformly mix the above components of sintering layer slurry to prepare sintering layer slurry with a solid content of 50-70%;

[0040] Preferably, step S2 prepares a sintering layer slurry having a solid content of 55-65%;

[0041] S3, coating the sintering layer slurry on the aluminum foil, baking for 20 to 40 minutes, and then compacting the sintering layer slurry at 1 to 3 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0042] Preferably, the thickness of the sintering layer slurry applied in step S3 is in the range of 50 to 150 μm;

[0043] Preferably, step S3 compacts the sintering layer slurry at 1.5 atmospheres;

[0044] S4, sintering, firstly, heating the aluminum foil coated with the sintering layer slurry to 180-220°C, keeping the temperature for 20-40 minutes, then heating the temperature to 400-500°C at a rate of 1°C / min, keeping the temperature for 1-4 hours, and finally raising the temperature to 580-660°C, keeping the temperature for 1-4 hours to form a laminated foil for capacitors;

[0045] Preferably, the sintering process in step S4 is performed under the protection of nitrogen or an inert gas.

[0046] A fifth aspect is a laminated foil produced using the above production method.

[0047] A sixth aspect is an aluminum capacitor made of the above-mentioned laminated foil.

[0048] The beneficial effects of the above technical solution are:

[0049] The present application designs and synthesizes a modified silane coupling agent with a special star-shaped topological structure, wherein the siloxane groups are distributed at the ends of the star-shaped branches, and the modified silane coupling agent and a hydroxyl-containing organic resin are used as a binder to prepare a sintered layer slurry. The modified silane coupling agent with a star-shaped topological structure provides more reaction sites between inorganic substances and organic resins, and the sintered layer slurry is coated on the oxide film on the surface of the aluminum foil to better fill and coat its defects. Therefore, the prepared laminated foil has higher bending resistance, hydration resistance and leakage resistance. DETAILED DESCRIPTION

[0050] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0051] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0052] If the specific experimental conditions are not specified in the examples, they are usually based on the conventional conditions in the field or the conditions recommended by the reagent company; the materials, reagents, etc. used in the examples can be purchased through commercial channels unless otherwise specified.

[0053] Example 1

[0054] Preparation of modified silane coupling agent: amino-terminated polyamide-amine dendrimer CYD-110A (Weihai Chenyuan Molecular New Materials Co., Ltd., molecular formula: C 62 H 128 N 26 O 12 , the number of terminal amino groups is 8) 71.5g (0.05mol) was dissolved in 60mL ethyl acetate, 98.8g (0.4mol) of isocyanatepropyltriethoxysilane (IPTS) was added, the temperature was raised to 85℃ and refluxed for 1.5h, then the temperature was lowered to 40℃ and the solvent was distilled off under reduced pressure.

[0055] Example 2

[0056] Preparation of modified silane coupling agent: 71.5 g (0.05 mol) of CYD-110A was dissolved in 60 mL of ethanol, 188.8 g (0.8 mol) of glycidyloxypropyltrimethoxysilane (KH-560) was added, the temperature was raised to 75°C and refluxed for 2 h, then the temperature was lowered to 40°C and the solvent was removed by distillation under reduced pressure.

[0057] Example 3

[0058] Preparation of modified silane coupling agent: amino-terminated polyamide-amine dendrimer CYD-120A (Weihai Chenyuan Molecular New Materials Co., Ltd., molecular formula: C 142 H 288 N 58 O 28 , the number of terminal amino groups is 16) 162.8g (0.05mol) was dissolved in 110mL of ethyl acetate, 197.6g (0.8mol) of isocyanatepropyltriethoxysilane (IPTS) was added, the temperature was raised to 85℃ and refluxed for reaction for 3 seconds, then the temperature was lowered to 40℃ and the solvent was distilled off under reduced pressure.

[0059] Example 4

[0060] Preparation of modified silane coupling agent: 162.8 g (0.05 mol) of CYD-120A was dissolved in 130 mL of isopropanol, 377.6 g (1.6 mol) of glycidyloxypropyltrimethoxysilane (KH-560) was added, the temperature was raised to 85°C and refluxed for 4 h, then the temperature was lowered to 40°C and the solvent was removed by distillation under reduced pressure.

[0061] Example 5

[0062] Preparation of modified silane coupling agent: Hydroxyl-terminated polyamide-amine dendrimer CYD-100H (Weihai Chenyuan Molecular New Materials Co., Ltd., molecular formula: C 22 H 44 N6O8, number of terminal hydroxyl groups: 4) 52.1 g (0.1 mol) was dissolved in 50 mL of ethanol, 98.8 g (0.4 mol) of isocyanatepropyltriethoxysilane (IPTS) was added, the temperature was raised to 75°C and refluxed for 3 h, then the temperature was lowered to 40°C and the solvent was removed by distillation under reduced pressure.

[0063] Example 6

[0064] Preparation of modified silane coupling agent: Hydroxyl-terminated polyamide-amine dendrimer CYD-110H (Weihai Chenyuan Molecular New Materials Co., Ltd., molecular formula: C 62 H 120 N 18 O 20, the number of terminal hydroxyl groups is 8) 71.9g (0.05mol) was dissolved in 50mL of ethanol, 98.8g (0.4mol) of isocyanatepropyltriethoxysilane (IPTS) was added, the temperature was raised to 75℃ and refluxed for 3h, then the temperature was lowered to 40℃ and the solvent was distilled off under reduced pressure.

[0065] Example 7

[0066] Preparation of modified silane coupling agent: Dissolve 55.5 g (0.2 mol) of triglycidyl p-aminophenol (AFG-90 epoxy resin) in 100 mL of isopropanol, add 205 g (0.6 mol) of bis(3-trimethoxysilylpropyl)amine (KH170), heat to 80 ° C and reflux for 3 h, then cool to 40 ° C and remove the solvent by reduced pressure distillation.

[0067] Example 8

[0068] Preparation of modified silane coupling agent: Dissolve 60.5 g (0.2 mol) of trimethylolpropane triglycidyl ether in 100 mL of isopropanol, add 205 g (0.6 mol) of bis(3-trimethoxysilylpropyl)amine (KH170), heat to 80 ° C and reflux for 3 h, then cool to 40 ° C and remove the solvent by reduced pressure distillation.

[0069] Example 9

[0070] Preparation of modified silane coupling agent: Carboxyl-terminated polyamide-amine dendrimer CYD-100C (Weihai Chenyuan Molecular New Materials Co., Ltd., molecular formula: C 38 H 64 N 10 O 16 , the number of terminal carboxyl groups is 4) 91.7g (0.1mol) was dissolved in 100mL butyl acetate, 99.2g (0.42mol) of glycidyloxypropyltrimethoxysilane (KH-560) and 0.5g of hexadecyltrimethylammonium bromide were added as epoxy ring-opening catalysts, the temperature was raised to 120℃ and refluxed for 4h, then the temperature was lowered to 50℃ and the solvent was distilled off under reduced pressure.

[0071] Example 10

[0072] Preparation of modified silane coupling agent: isocyanate-terminated HDI trimer 50.5 g (0.1 mol) of N 3800 was dissolved in 50 mL of ethyl acetate, and 102.5 g (0.3 mol) of bis(3-trimethoxysilylpropyl)amine (KH170) was added. The mixture was heated to 75°C and refluxed for 3 h. The mixture was then cooled to 40°C and the solvent was removed by distillation under reduced pressure.

[0073] Example 11 Preparation of laminated foil

[0074] S1. Pretreatment of the substrate: wipe the surface of the aluminum foil with 95% ethanol to remove the oil stains on the surface, and then put it into a 0.1M hydrochloric acid solution for slight corrosion to remove the oxide film formed on the surface of the substrate;

[0075] S2, preparation of sintering layer slurry, mixing 40g of modified silane coupling agent prepared in Example 1 with 5g of polyethylene glycol PEG-1000 and 95g of polyvinyl alcohol PVA-1799 particles, adding 180g of aluminum powder with an average particle size of 1 μm, and using 230g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 58%;

[0076] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 90 μm, baking at 120° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0077] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 450°C at a rate of 1°C / min and kept warm at 450°C for 1 hour. Finally, the temperature is raised to 620°C and kept warm at 620°C for 3 hours to form a laminated foil for capacitors.

[0078] Example 12 Preparation of laminated foil

[0079] S1 is the same as Example 11;

[0080] S2, preparation of sintering layer slurry, mixing 35g of modified silane coupling agent prepared in Example 2 with 5g of polyethylene glycol PEG-1000 and 90g of polyvinyl alcohol PVA-1799 particles, adding 170g of aluminum powder with an average particle size of 1 μm, and using 200g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 60%;

[0081] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 75 μm, baking at 120° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0082] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 430°C at a rate of 1°C / min and kept warm at 430°C for 1.5 hours. Finally, the temperature is raised to 630°C and kept warm at 630°C for 3 hours to form a laminated foil for capacitors.

[0083] Example 13 Preparation of laminated foil

[0084] S1 is the same as Example 11;

[0085] S2, preparation of sintering layer slurry, mixing 45g of modified silane coupling agent prepared in Example 3 with 5g of polyethylene glycol PEG-1000 and 105g of polyvinyl alcohol PVA-1799 particles, adding 185g of aluminum powder with an average particle size of 1 μm, and using 250g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 57.6%;

[0086] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 100 μm, baking at 140° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0087] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 480°C at a rate of 1°C / min and kept warm at 480°C for 2 hours. Finally, the temperature is raised to 630°C and sintered at 630°C for 3 hours to form a laminated foil for capacitors.

[0088] Example 14 Preparation of laminated foil

[0089] S1 is the same as Example 11;

[0090] S2, preparation of sintering layer slurry, mixing 40g of modified silane coupling agent prepared in Example 4 with 5g of polyethylene glycol PEG-1000 and 100g of polyvinyl alcohol PVA-1799 particles, adding 180g of aluminum powder with an average particle size of 1 μm, and using 250g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 56.5%;

[0091] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 90 μm, baking at 130° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0092] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 500°C at a rate of 1°C / min and kept warm at 500°C for 2 hours. Finally, the temperature is raised to 620°C and kept warm at 620°C for 3 hours to form a laminated foil for capacitors.

[0093] Example 15 Preparation of laminated foil

[0094] S1 is the same as Example 11;

[0095] S2, preparation of sintering layer slurry, mixing 40g of modified silane coupling agent prepared in Example 5 with 5g of polyethylene glycol PEG-1000 and 95g of polyvinyl alcohol PVA-1799 particles, adding 180g of aluminum powder with an average particle size of 1 μm, and using 230g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 58%;

[0096] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 120 μm, baking at 120° C. for 40 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0097] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 480°C at a rate of 1°C / min and kept warm at 480°C for 2 hours. Finally, the temperature is raised to 630°C and sintered at 630°C for 3 hours to form a laminated foil for capacitors.

[0098] Example 16 Preparation of laminated foil

[0099] S1 is the same as Example 11;

[0100] S2, preparation of sintering layer slurry, mixing 50g of the modified silane coupling agent prepared in Example 6 with 5g of polyethylene glycol PEG-1000 and 110g of polyvinyl alcohol PVA-1799 particles, adding 195g of aluminum powder with an average particle size of 1 μm, and using 240g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 60%;

[0101] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 125 μm, baking at 130° C. for 40 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0102] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 480°C at a rate of 1°C / min and kept warm at 480°C for 2.5 hours. Finally, the temperature is raised to 650°C and sintered at 650°C for 3 hours to form a laminated foil for capacitors.

[0103] Example 17 Preparation of laminated foil

[0104] S1 is the same as Example 11;

[0105] S2, preparation of sintering layer slurry, mixing 40g of modified silane coupling agent prepared in Example 7 with 5g of polyethylene glycol PEG-1000 and 100g of polyvinyl alcohol PVA-1799 particles, adding 185g of aluminum powder with an average particle size of 1 μm, and using 240g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 57.9%;

[0106] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 95 μm, baking at 120° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0107] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 480°C at a rate of 1°C / min and kept warm at 480°C for 1.5 hours. Finally, the temperature is raised to 650°C and kept warm at 650°C for 3 hours to form a laminated foil for capacitors.

[0108] Example 18 Preparation of laminated foil

[0109] S1 is the same as Example 11;

[0110] S2, preparation of sintering layer slurry, mixing 45g of modified silane coupling agent prepared in Example 8 with 5g of polyethylene glycol PEG-1000 and 95g of polyvinyl alcohol PVA-1799 particles, adding 180g of aluminum powder with an average particle size of 1 μm, and using 225g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 59.1%;

[0111] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 80 μm, baking at 120° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0112] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 430°C at a rate of 1°C / min and kept warm at 430°C for 2 hours. Finally, the temperature is raised to 610°C and kept warm at 610°C for 3 hours to form a laminated foil for capacitors.

[0113] Example 19 Preparation of laminated foil

[0114] S1 is the same as Example 11;

[0115] S2, preparation of sintering layer slurry, mixing 45g of modified silane coupling agent prepared in Example 9 with 5g of polyethylene glycol PEG-1000 and 100g of polyvinyl alcohol PVA-1799 particles, adding 185g of aluminum powder with an average particle size of 1 μm, and using 225g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 59.8%;

[0116] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 90 μm, baking at 120° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0117] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 460°C at a rate of 1°C / min and kept warm at 460°C for 2 hours. Finally, the temperature is raised to 600°C and sintered at 600°C for 4 hours to form a laminated foil for capacitors.

[0118] Example 20 Preparation of laminated foil

[0119] S1 is the same as Example 11;

[0120] S2, preparation of sintering layer slurry, mixing 40g of modified silane coupling agent prepared in Example 10 with 5g of polyethylene glycol PEG-1000 and 95g of polyvinyl alcohol PVA-1799 particles, adding 180g of aluminum powder with an average particle size of 1 μm, and using 225g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 58.7%;

[0121] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 90 μm, baking at 120° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0122] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 460°C at a rate of 1°C / min and kept warm at 460°C for 2 hours. Finally, the temperature is raised to 600°C and sintered at 600°C for 4 hours to form a laminated foil for capacitors.

[0123] Comparative Example 1 Preparation of laminated foil

[0124] S1 is the same as Example 11;

[0125] S2, preparation of sintering layer slurry, mixing silane coupling agent aminopropyl triethoxysilane (KH550) 45g with polyethylene glycol PEG-1000 5g and polyvinyl alcohol PVA-1799 particles 95g, adding 180g aluminum powder with an average particle size of 1μm, and using 235g solvent isopropanol to prepare a sintering layer slurry with a solid content of 58.0%;

[0126] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 90 μm, baking at 120° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0127] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 450°C at a rate of 1°C / min and kept warm at 450°C for 2 hours. Finally, the temperature is raised to 620°C and sintered at 620°C for 3 hours to form a laminated foil for capacitors.

[0128] Comparative Example 2 Preparation of laminated foil

[0129] S1 is the same as Example 11;

[0130] S2, preparation of sintering layer slurry, mixing silane coupling agent glycidyl ether oxypropyl trimethoxy silane (KH560) 45g with polyethylene glycol PEG-1000 5g and polyvinyl alcohol PVA-1799 particles 95g, then adding 180g aluminum powder with an average particle size of 1μm, and using 235g solvent isopropanol to prepare a sintering layer slurry with a solid content of 58.0%;

[0131] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 90 μm, baking at 120° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0132] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 450°C at a rate of 1°C / min and kept warm at 450°C for 2 hours. Finally, the temperature is raised to 620°C and sintered at 620°C for 3 hours to form a laminated foil for capacitors.

[0133] Comparative Example 3

[0134] S1 is the same as Example 11;

[0135] S2, preparation of sintering layer slurry, 25g of aminopropyl triethoxysilane (KH550) and 25g of glycidyloxypropyl trimethoxysilane (KH560) were mixed with 5g of polyethylene glycol PEG-1000 and 105g of polyvinyl alcohol PVA-1799 particles, 190g of aluminum powder with an average particle size of 1 μm was added, and 250g of solvent isopropanol was used to prepare a sintering layer slurry with a solid content of 58.3%;

[0136] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 90 μm, baking at 120° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0137] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 460°C at a rate of 1°C / min and kept warm at 460°C for 2 hours. Finally, the temperature is raised to 630°C and kept warm at 630°C for 3 hours to form a laminated foil for capacitors.

[0138] Comparative Example 4

[0139] S1 is the same as Example 11;

[0140] S2, preparation of sintering layer slurry, mixing 40g of modified silane coupling agent prepared in Example 1 with 5g of polyethylene glycol PEG-1000 and 95g of polyvinyl alcohol PVA-1799 particles, adding 180g of aluminum powder with an average particle size of 1 μm, and using 230g of solvent isopropanol to prepare a sintering layer slurry with a solid content of 58%;

[0141] S3, coating the sintering layer slurry on the aluminum foil, the thickness of the sintering layer slurry is 90 μm, baking at 120° C. for 30 min, and then compacting at 1.5 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry;

[0142] S4, sintering. The sintering process is carried out under nitrogen protection. First, the aluminum foil coated with the sintering layer slurry is heated to 200°C and kept warm for 30 minutes. Then the temperature is raised to 450°C at a rate of 1°C / min and kept warm at 450°C for 1 hour. Finally, the temperature is raised to 540°C and kept warm at 540°C for 3 hours to form a laminated foil for capacitors.

[0143] Test Section

[0144] For the laminated foils prepared in Examples 11-20 and Comparative Examples 1-4, the tensile strength, bending strength and hydration resistance test of the laminated foils for capacitors were tested using the method of standard SJ / T 11140-2012. The hydration resistance test method is to immerse the laminated foil in 500 mL of pure water above 95°C for 600 min (10 h), and test its withstand voltage and boost time values. The time taken for the laminated foil to boost the voltage to 90% of the rated withstand voltage according to the specified current is the boost time Tr. 600 .

[0145] The leakage current of the laminated foil was tested using the ASTM D257 method, and the adhesion of aluminum powder on the laminated foil was tested using the ASTM D3359 method.

[0146] The test results of the laminated foils prepared in Examples 11-20 and Comparative Examples 1-4 are shown in Table 1.

[0147] Table 1

[0148]

[0149] From the analysis of the experimental results in Table 1, it can be seen that in Example 11-20, which uses a modified silane coupling agent with a star-shaped topology structure and a surfactant PEG, aluminum powder, and a hydroxyl-containing resin polyvinyl alcohol to prepare a sintered layer slurry, the laminated aluminum foil prepared by coating and sintering has higher bending strength and lower leakage current, and the boost time of the laminated aluminum foil after boiling in water for 600 minutes is shorter, indicating that the prepared laminated foil has stronger hydration resistance and better quality. Among them, the modified silane coupling agent with a star-shaped topology structure provides more reaction sites between inorganic substances and hydroxyl-containing organic resins, and the filling and coating effects of defects on the surface oxide film of the aluminum foil are better when coated on the surface oxide film of the aluminum foil, and the formation of defects on the surface oxide film of the aluminum foil during high-temperature sintering can be effectively alleviated. The terminal groups of small molecule silane coupling agents such as KH550 and KH560 are shorter, and there are fewer reaction sites with the organic resin, and the intermolecular force is weak, so the corresponding laminated foil has low bending strength and higher leakage current, and the performance is not as good as the laminated foil prepared by Example 11-20. Among them, the laminated foils (Examples 11, 13 and 20) using the modified silane coupling agent containing urea bonds in Examples 1, 3 and 10 have lower leakage current, shorter voltage rise time and relatively better performance.

[0150] In addition, too low a sintering temperature also has a great influence on the performance of the prepared laminated foil. From the performance comparison between Comparative Example 4 and Example 11, it can be seen that the laminated foil is prepared using the same modified silane coupling agent and sintering layer slurry. The sintering temperature of Comparative Example 4 does not exceed 550°C, and the leakage current of the prepared laminated foil is significantly higher, and the hydration resistance performance is significantly reduced. This is because the sintering temperature is too low, the content of amorphous aluminum oxide in the aluminum powder increases during the sintering process, and the content of α-alumina in the crystal structure decreases, which affects the quality of the entire oxide film, especially the ability of the laminated foil to resist hydration damage. It has a significant impact, which is specifically reflected in the large leakage current and the extended boost time of the hydration resistance test.

[0151] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.

Claims

1. A modified silane coupling agent, characterized in that: The silane coupling agent has a star topology structure, and the functional group at the end is a siloxane group, wherein the star topology structure is defined as 3 or more linear branches connected to a central core in sequence, and the functional group at the end of the linear branch is a siloxane group; Furthermore, the modified silane coupling agent is obtained by reacting a polyamine having a star topology structure with an epoxy-containing silane coupling agent or an isocyanate-containing silane coupling agent; Furthermore, the modified silane coupling agent is obtained by reacting a polyol having a star topology structure with an isocyanate-containing silane coupling agent; Furthermore, the modified silane coupling agent is obtained by reacting a polyacid having a star topology structure with an epoxy-containing silane coupling agent; Furthermore, the modified silane coupling agent is obtained by reacting a polyglycidyl ether having a star topology structure with a silane coupling agent containing an amino group or an imino group; Furthermore, the modified silane coupling agent is obtained by reacting a polyisocyanate having a star topology structure with a silane coupling agent containing an amino group or an imino group.

2. The method for preparing the modified silane coupling agent according to claim 1, comprising: The silane coupling agent is grafted onto a central core with a star-shaped topology.

3. The preparation method according to claim 2, characterized in that: The groups for grafting reaction between the silane coupling agent and the central core include: epoxy group, carboxyl group, hydroxyl group, isocyanate group, amino group or imino group.

4. The preparation method according to claim 2, characterized in that: The grafting reaction includes but is not limited to: reaction between epoxy group and amino group or imino group, reaction between epoxy group and carboxyl group, reaction between amino group or imino group and isocyanate group, reaction between hydroxyl group and isocyanate group; Preferably, the total molar amount of reactive groups on the silane coupling agent is greater than or equal to the total molar amount of reactive groups on the central core.

5. A sintering layer slurry, comprising: The modified silane coupling agent according to claim 1, a hydroxyl-containing resin, aluminum powder or aluminum alloy powder and a solvent; The hydroxyl-containing resin includes: one or more combinations of polyvinyl alcohol resin, polyester resin, epoxy resin, phenolic resin, phenolic epoxy resin, and hydroxyl acrylic resin; The solvent includes one or more of methanol, ethanol, isopropanol, ethylene glycol, glycerol, ethyl acetate, and butyl acetate; Preferably, the particle size of the aluminum powder or aluminum alloy powder is in the range of 100 nm to 10 μm.

6. The sintering layer slurry according to claim 5, characterized in that: The sintering layer slurry also includes a nonionic surfactant.

7. A method for preparing a laminated foil, characterized in that: The preparation method comprises: coating the sintering layer slurry according to any one of claims 5 to 6 on at least one side of a substrate, and then gradually increasing the temperature for sintering, wherein the substrate is aluminum foil.

8. The preparation method according to claim 7, characterized in that: The preparation method comprises the following specific steps: S1. Pretreatment of the substrate: remove oil stains on the substrate surface, and use 0.1M dilute hydrochloric acid or dilute sulfuric acid to slightly corrode and remove the metal oxide film on the substrate surface; S2. Preparation of sintering layer slurry: uniformly mix the above components of sintering layer slurry to prepare sintering layer slurry with a solid content of 50-70%; Preferably, step S2 prepares a sintering layer slurry having a solid content of 55-65%; S3, coating the sintering layer slurry on the aluminum foil, baking for 20 to 40 minutes, and then compacting the sintering layer slurry at 1 to 3 atmospheres, thereby preparing an aluminum foil coated with the sintering layer slurry; Preferably, the thickness of the sintering layer slurry applied in step S3 is in the range of 50 to 150 μm; Preferably, step S3 compacts the sintering layer slurry at 1.5 atmospheres; S4, sintering, firstly, heating the aluminum foil coated with the sintering layer slurry to 180-220°C, keeping the temperature for 20-40 minutes, then heating the temperature to 400-500°C at a rate of 1°C / min, keeping the temperature for 1-4 hours, and finally raising the temperature to 580-660°C, keeping the temperature for 1-4 hours to form a laminated foil for capacitors; Preferably, the sintering process in step S4 is performed under the protection of nitrogen or an inert gas.

9. A laminated foil produced by the production method according to any one of claims 7 to 8.

10. An aluminum capacitor produced using the laminated foil according to claim 9.